ANALISA DAYA DUKUNG CERUCUK GALAM PADA PERKERASAN RIGID DI RUAS JALAN TATAH BANGKAL - Yusgian Yusgian; Muhammad Afief Ma'ruf (Universitas Lambung Mangkurat, 2021)
Banjarmasin is known as the city of a thousand rivers where the soil is a soft soil with a very low bearing capacity. The Tatah Bangkal road section from sta 0+450 to sta 0+750 is planned to use rigid pavement with a thickness of 28 cm, but during the implementation of galam pile with a length of 4 m, the ones that came to the field was only 3.8 m and when it is tapered, the length is only 3.6 m. In addition, driving the pile directly on the road surface without excavating could not be carried out because the pile was broken and damaged when it was driven to a depth of 1,0 m. The purpose of this analysis is to obtain the length of the galam pile that can be driven into the grained pavement layer without digging until the soil is soft, but its bearing capacity is still achieved to withstand rigid pavement loads and traffic loads. After going through several piling experiments, it turned out that the galam cone was 3.5 m long and the grained pavement was dug up to a depth of 30 cm and the galam pile was not broken.